Viral proteins function as ion channels - Wang, Kai (Biochim Biophys Acta Biomembr, 2011)
Viral ion channels are short membrane proteins with 50–120 amino acids and play an important role either in regulating virus replication, such as virus entry, assembly and release or modulating the electrochemical balance in the subcellular compartments of host cells. This review summarizes the recent advances in viral encoded ion channel proteins (or viroporins), including PBCV-1 KcV, influenza M2, HIV-1 Vpu, HCV p7, picornavirus 2B, and coronavirus E and 3a. We focus on their function and mechanisms, and also discuss viral ion channel protein serving as a potential drug target.